Effect of seaweed (Eucheuma cottonii) addition on the physical, chemical and hedonic properties of peas-based meatballs in comparison with conventional meatball - Afidah, Ulil; Jannah, Annisa Findy Nur; Rifai, Muhamad; Abduh, Setya Budi Muhammad; Legowo, Anang Mohamad (Journal of Advanced Veterinary Research, 2025)
Vegetable proteins, such as those derived from peas (Pisum sativum L.), lack a naturally fibrous structure, resulting in a texture that differs significantly from conventional meat when processed into meat analogues like meatballs. Seaweed, known for its structural complexity and dietary fiber content, was explored in this study as a functional ingredient to enhance the texture and overall quality of pea-based meatballs. The objective was to evaluate the effects of seaweed flour addition on the physical, chemical, sensory, and preference properties of these plant-based products. Seaweed was added at concentrations of 0, 1, 1.5, and 2% (w/w) into a mixture of meatball (pea paste, tapioca, and spices). Conventional beef meatballs were used as the control. The samples were evaluated for moisture, protein, fat content, water holding capacity, cooking loss, textural attributes (hardness, cohesiveness, springiness, adhesiveness), crude fiber, yield, sensory quality, and consumer preference. Data were analyzed using one-way ANOVA and principal component analysis (PCA). Results showed that seaweed flour addition up to 2% significantly increased the moisture and protein contents, WHC, texture parameters, yield, and fiber content, while reducing cooking loss compared to the control pea-based meatballs, with no significant effect on fat content (p > 0.05). Compared to beef meatballs, pea-based meatballs had lower values in most quality parameters but showed higher hardness, springiness, adhesiveness, and fiber. PCA confirmed distinct characteristics between pea- and beef-based meatballs, in agreement with the ANOVA findings.